2010
DOI: 10.1007/s11002-010-9117-y
|View full text |Cite
|
Sign up to set email alerts
|

The value of celebrity endorsements: A stock market perspective

Abstract: Are celebrity endorsements worthwhile investments in advertising? To answer this question, we analyze a unique sample of 101 announcements made between 1996 and 2008 by firms listed in the USA. Internet is the main medium of communication for these announcements. We employ event study methodology and document statistically insignificant abnormal returns around the announcement dates. This finding is consistent with the notion that the incremental benefits from celebrity endorsements closely match the increment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
52
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 45 publications
6
52
2
Order By: Relevance
“…The literature on the topic finds a general positive effect on the endorsing firm's market value (Agrawal and Kamakura, 1995;Mathur et al, 1997), with some exceptions, such as the results of Ding et al (2011), which stress the fact that the expenses incurred may offset the benefits derived from the endorsement strategy.…”
Section: Introductionmentioning
confidence: 99%
“…The literature on the topic finds a general positive effect on the endorsing firm's market value (Agrawal and Kamakura, 1995;Mathur et al, 1997), with some exceptions, such as the results of Ding et al (2011), which stress the fact that the expenses incurred may offset the benefits derived from the endorsement strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Farrell, Karels, Monfort, & McClatchey (2000) explore the impact of Tiger Wood's tournament performance in 1996-1997 on Nike's firm value. Further, Ding, Molchanov, & Stork (2010) claime that celebrity endorsements restricted to technological products led to significant positive abnormal returns. Fizel, Mcneil, & Smaby (2008) examine 148 conventional athlete endorsements excluding mega-stars--their results showed that these endorsements had an insignificant impact on the firm's market value.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…The celebrity-endorsement strategy has been widely adopted in the field of product advertising since its inception (Bailey, 2007;Biswas, Biswas, & Das, 2006;Ding, Molchanov, & Stork, 2010;Erdogan, 1999;McCracker, 1989;Seno & Bryan, 2007). Many researchers have investigated the effectiveness of these types of strategies.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Other events or announcements that have the tendency of triggering volatility of the stock market include rail accidents (Walker et al, 2006), product and market diversification (Jones & Danbolt, 2005), mergers and acquisitions (Liang, 2013), punitive damages (Lott & Karpoff, 1998), new product introduction , stock split (Subaih, 2013), natural disasters (Maierhofer, 2011), awards (Bu & Tian, 2012), corporate press releases (Neuhierl et al, 2013), media and celebrity endorsements (Ding et al, 2011;Doukas, 2013) and supply chain disruptions (Hendricks & Singhal, 2008). The impact of most of these announcements or events on stock performance is usually firm-specific, industry-specific or geographic-specific.…”
Section: Introductionmentioning
confidence: 99%